Rational Emotive Behavior Counseling with Mindfulness Techniques (Ruqyah Meditation) to Increase The Noble Character of Students - Ach. Firman Ilahi; Kadek Suranata; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This research was conducted to develop and test the acceptability of Counseling Guidance books with Indonesian culture-based mindfulness techniques (Ruqyah Meditation) to improve the noble character of students in Islamic boarding schools and to determine its effectiveness in its application. This study uses research and development methods using the 4D model by Thiagarajan. Then carried out further analysis using Aiken's validity with a validity result of 0.94 which indicates a high level of validity. So that this guidebook meets the criteria of acceptance in the use of guidance and counseling services in schools. To test its effectiveness, it was tested on students at school and involved 14 students in it using one group pretest and posttest, using the N-Gain score calculation formula of 0.65 which has a sufficient level of effectiveness. So that this guidebook is quite effective in improving the noble character of students in Islamic boarding schools.